DRUG UTILISATION STUDY OF STROKE AND OTHER PATIENTS ADMITTED TO GENERAL WARD OF NEUROLOGY UNIT AT QUATERNARY CARE PRIVATE HOSPITAL - Wagle, Laxman; Thomas, Abel Abraham; Shrestha, Sunil (International Journal of Current Pharmaceutical Research, 2017)
Objective: To study the profile of the patient, the pattern of their illness and their drug use patterns attending to general ward of quaternary care hospital. Methods: Prospective observational study of 2 mo was performed at neurology unit of the quaternary care private hospital, India. Patients aged above 20 y with at least one neurological drug in prescription were included to observe their demographic profile, illness pattern and drug use. The data was analysed and summarised as frequency and percentage using microsoft excel and presented as tables. Results: Among 60 patient that were enrolled, more were males (N=33, 55%) than females (N=27, 45%) and within the age group of 60-70 y (N=22, 36.67%). The majority of patients were diagnosed with strokes (N= 48, 80%) where the cerebrovascular accident was most common (N=16, 26.66%). Males (N=29, 60.4%) were more prone to get stroke than females (N=19,39.6%). An average number of drugs per prescription was 5.7, the percentage of antibiotics, generic drugs and injections were 36.6%, 0.05% and 44.14% respectively. A total of 28 different drug classes with 61 different drugs was utilised. Fourteen drug classes had been accounted for 90% of drugs utilisation. Clopidegrol+Aspirin have frequently used the drug. Conclusion: Most people attending neurology unit were elderly. Stroke occupies 1st list for the burden. Average drugs for neurology visit remain high. Wide types of drug classes are utilised in neurological wards